The Imagination of Resemblance. Landscape and Mimesis in Contemporary Painting - Giambrone, Giulia (Aesthetica Preprint, 2024)
The representation of the landscape in contemporary painting calls into question a renewed figurative image. Bound to an imagery largely belonging to a reality different than the natural one, the mimetic rendering is nevertheless predominant. The landscape is characterised by the restriction of space in the framework and the relationship with the human figure inside, hiding the dissolution of the subject. Both, the natural restriction of the space and the flatness of the image as well as the mimetic elision of the subject are elements already identified by Michel Foucault in Manet’s paintings and in the post-Renaissance episteme exemplified in a representation by the concept of imagination of resemblance. Manet’s spatial conception traces a common thread all the way to the greatest landscape painter of the contemporary age, David Hockney.